Analysis of Character Education Implementation at MI Al-Huda Karangnongko - Ru'uliyanah Sabrianti; Muh. Wasith Achadi (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to analyze the implementation of character education at MI Al-Huda Karangnongko, covering planning, implementation, evaluation, and outcomes of religious values-based programs. A descriptive qualitative approach was employed through in-depth interviews, participatory observation, and documentation. The primary informant was the principal of MI Al-Huda Karangnongko. Data analysis used the interactive model of Miles, Huberman, and Saldana (2014). The findings reveal that character education is integrated through daily worship habituation (Duha, Zuhur, and Asar prayers), a four-times-weekly Quranic tahfidz program, monthly Minggu Legi recitation events, and hadroh extracurricular activities. The program has been standardized since 2019 under the current principal's leadership in collaboration with the UMI institution, which provides 16 certified tahfidz instructors. Structured evaluation is conducted every Wednesday for tahfidz and every Friday for all activities. Positive impacts are reflected in improved academic and religious achievement, awards as adiwiyata and healthy madrasah, and enrollment growth from two to three classes per cohort. Enabling factors include full teacher and staff engagement and UMI partnership, while the main inhibiting factor is insufficient parental support.